PERLINDUNGAN HUKUM TERHADAP PEMODAL DALAM PENAWARAN EFEK MELALUI LAYANAN URUN DANA BERBASIS TEKNOLOGI INFORMASI (Studi Perbandingan di Indonesia dan Amerika Serikat) - Monica Blazinky; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2021)
Some time ago a new legal institution emerged in the form of a crowdfunding service agreement through an information technology-based stock offering. This form is the result of the adoption of business arrangements in several developed countries carried out by business people by involving technological sophistication. This crowdfunding service is growing rapidly in Indonesia, there are concerns about legal protection for users, including investors. The risk of fraud is quite high because the issuers in the Securities Crowdfunding are start-up companies that can be shaken and go bankrupt and the investors are novice investors. Therefore, the issue of legal protection becomes an urgent matter to be studied so that investors do not experience things that can be detrimental. Investor protection in SCF services is a concern because in the next 10 years SCF will become one of the platforms for MSMEs and start-up companies to get capital. The author uses normative research methods, with the help of primary and secondary legal materials. The results of the study explain that legal protection for investors in SCF services in Indonesia is a very important matter to be studied. In contrast to the United States, which has implemented a secondary market that helps investors to sell their securities and easily withdraw them. But some time ago, Indonesia just implemented the secondary market. This is done to protect investors, but the regulation POJK 57/POJK.04/2020 has not regulated the mechanism for implementing the secondary market. So, the OJK needs to optimize the regulation so that in the future the legal protection and mechanism will be adequate.